Personal Characteristics and Banking Behaviour of Customers: Further Evidence from Usmanu Danfodiyo University Sokoto-Nigeria - Aliero, Haruna Mohammed; Aliero, Ibrahim Hussaini; Zakariyya’u, Sulaiman (Journal of Accounting, Business and Finance Research, 2017)
“This study examines the extent to which customers’ personal characteristics have influence on the banking bahaviour of customers. The study uses primary data which was collected from the Usmanu Danfodiyo University Sokoto. A sample of 383 respondents was used cutting across staff, students and petty business operators within the community. The study uses Logistic regression model to analyse the data. The results of the study indicated that age, marital status, and occupation have negative influence on the banking bahviour of customers while, educational qualification and monthly income have positive influence. The study therefore recommends that those factors with positive influence should be closely watched whenever banks are looking for customers in the community and other communities with similar features.”